(untitled) (Bangladesh Veterinarian, 2010)
The production traits of Red Chittagong Cattle (RCC) were studied using two diets: A [Urea-molasses-rice straw (UMRS), Green Grass and Concentrate] and B [Rice straw, Green Grass and Concentrate]. In cows fed diets A and B, birth weights of calves were 15.2 and 14.1 kg (P<0.05), daily milk yield 2.0 and 2.0 kg (P>0.05), lactation length 254.8 and 247.1 days (P>0.05), age at first oestrus 28.4 and 25.6 months (P<0.05), number of services per pregnancy 1.6 and 2.5 (P<0.05), onset of postpartum oestrus 141.3 and 109.3 days (P<0.05), calving interval 14.2 and 13.3 months (P<0.05), semen volume per ejaculation 3.0 and 3.7 ml (P<0.05), mass activity of sperm 58.6 and 68.4% (P<0.01) and sperm concentration 709.1 and 1289.0 million/ml (P<0.01), respectively. DOI: 10.3329/bvet.v26i2.4954 Bangl. vet. 2009. Vol. 26, No. 2, 74-79